Pengaruh Substitusi Bahan Sumber Energi dengan Tepung Tongkol Jagung Hasil Fermentasi Probiotik Win Prob dan Imbuhan Zn Biokompleks dalam Pakan Konsentrat terhadap Protein Kasar Tercerna, Energi Tercerna dan TDN Sapi Bali Penggemukan - Halek, Hildegardis; Sulistijo, Edi Djoko; Amalo, Daud (Animal Agricultura, 2025)
This study examined the effect of rice bran and ground corn substitution levels with Win_prob probiotic fermented corn cob flour (TTJF) and the addition of Zn biocomplex in concentrate feed on the nutrient digestibility of fattening Bali cattle. A total of 12 male Bali cattle aged 1–1.5 years (147–189 kg; 168.08±15.50 kg; KV 9.22%) were tested with 4 treatments × 3 replicates: P0 (control); P1 (bran replaced with 25% TTJF and 15% ground corn); P2 (35% and 25%); P3 (45% and 35%); all treatments supplemented with 100 mg of bio-complexed Zn. Variables: digestible crude protein, digestible energy, and TDN; analysis using ANOVA. The mean showed a downward trend from P0 to P3, but was not significantly different (P>0.05). It was concluded that TTJF could be used up to 45% to replace bran and 35% to replace ground corn from the initial composition of 55% bran + 20% corn in the concentrate, without reducing the digestibility of protein, energy, and TDN in Bali cattle.